Stagnation-point flow towards a strecthing surface immersed in a micropolar fluid with prescribed surface heat flux - Nor Azizah M. Yacob,; Anuar Mohd Ishak, (Universiti Kebangsaan Malaysia, 2010)
The steady two dimensional boundary layer flow adjacent to the stagnation point on a stretching surface immersed in a micropolar fluid was investigated. The stretching and the free stream velocities were assumed to vary linearly from the stagnation point. The governing partial differential equations were transformed into ordinary differential equations before being solved numerically by a finite-difference scheme known as the Keller box method. Both assisting and opposing flows were considered. The boundary layer was formed when the free stream velocity exceeds the stretching velocity, whereas the inverted boundary layer was formed when the free stream velocity is less than the stretching velocity. The numerical results showed that the shear force decreased for micropolar fluid compared to Newtonian fluid, and in consequence decreased the heat transfer rate at the surface.